PERAN TRANSFORMASIONAL GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA DI ERA DIGITAL : STUDI DI SMAN 15 TAKENGON (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze the role of Islamic Education (PAI) teachers in developing students’ noble character at SMAN 15 Takengon through the framework of transformational leadership. Employing a qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that PAI teachers play a strategic role as moral agents who not only transmit religious knowledge cognitively but also shape students’ behavior and character through exemplary conduct, spiritual motivation, and individualized guidance. The application of transformational leadership is evident in four key dimensions: (1) idealized influence, reflected in teachers’ integrity and role modeling; (2) inspirational motivation, expressed through inspiring moral messages that enhance religious awareness; (3) intellectual stimulation, by encouraging critical reflection on contemporary moral issues; and (4) individualized consideration, through adaptive moral coaching tailored to students’ needs. Moreover, PAI teachers integrate digital media such as reflection videos and online forums to extend moral education beyond the classroom. Consequently, moral cultivation becomes not only an instructional process but also a lived culture embedded in students’ daily lives.